Synthesis of Polyfunctionalized Amino Furans with Long Conjugated Aromatic Systems Using Nucleophilic Aromatic Isocyanide - Mohammad Qandalee; Masoud Mokhtary; Sakineh Asghari; Mehrdad Mehrzadi (E-Journal of Chemistry)
Polyfunctionalized amino furans with long conjugated aromatic systems have been synthesized by three component reaction of aldehydes, acetylenic esters and aromatic nucleophilic isocyanide.